Case Report: “Dumbbell” giant right coronary artery ectasia with right atrial fistula - Shan, Jianggui; Wang, Heng; Xue, Song (Frontiers in Cardiovascular Medicine, 2025)
A 50-year-old female patient presented with a “dumbbell” giant right coronary artery ectasia, characterized by two artery dilation segments both reaching the level of a giant aneurysm with a normal segment between them. Computed tomography angiography showed a fistula sac in the right atrium. The vessel shape was a typical type IV (localized or segmental) coronary artery ectasia, which is rarely seen on true imaging. The patient had a 3-year history of chest tightness, without dyspnea, worsened by physical activity. Additional tests indicated that she had mitral valve regurgitation, superficial myocardial bridge, and anemia, all of which led to the development of her symptoms. She felt relieved after successful coronary artery fistula repair, mitral valvuloplasty, and fistula sac removal. At the 6-month follow-up, no complications were found according to echocardiography. Patients with coronary aneurysms can be asymptomatic in the early stage, while this case indicates that the dumbbell shape may be a developing stage of giant coronary aneurysm whose origin and close-fistula segments are influenced by separate hydrodynamics during ectasia or aneurysm formation.